2002
DOI: 10.1039/b206847h
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a nano-electrospray ionisation source for atmospheric pressure ion mobility spectrometry

Abstract: A nano-electrospray ionisation source has been designed and constructed for a high temperature ion mobility spectrometer. The drift cell was modified by replacement of the 63Ni atmospheric pressure chemical ionisation source with a tube lens/desolvation region and operated using commercial nano-electrospray capillaries. Ions were introduced into the drift region via a Bradbury-Nielson gate (pulse width 50 micros, repetition period 20 ms). A unidirectional flow of nitrogen was used as the drift gas at temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…However, after thorough and careful analysis, these opposite effects were attributed to the different ion transmission mechanisms which exist in ESI-IMS and ESI-MS. Our data showed that the general recognition of improved ionization efficiency at reduced flow rate for ESI-MS still held true in case of ESI-IMS despite ion signal loss was observed. Based on our ionization efficiency analysis, now we are able to understand why no substantial sensitivity improvement was observed for nano-ESI-IMS (use of >5mM analyte concentration) 23 as compared to nano-ESI-MS which shows at least two orders of magnitude signal enhancement over conventional ESI-MS. 14 Thus it seems necessary to further improve ionization efficiency for IMS in order to improve overall detection sensitivity. However, the inherent limitation of IMS is attributed to its low duty cycle (<1%).…”
Section: Discussionmentioning
confidence: 93%
“…However, after thorough and careful analysis, these opposite effects were attributed to the different ion transmission mechanisms which exist in ESI-IMS and ESI-MS. Our data showed that the general recognition of improved ionization efficiency at reduced flow rate for ESI-MS still held true in case of ESI-IMS despite ion signal loss was observed. Based on our ionization efficiency analysis, now we are able to understand why no substantial sensitivity improvement was observed for nano-ESI-IMS (use of >5mM analyte concentration) 23 as compared to nano-ESI-MS which shows at least two orders of magnitude signal enhancement over conventional ESI-MS. 14 Thus it seems necessary to further improve ionization efficiency for IMS in order to improve overall detection sensitivity. However, the inherent limitation of IMS is attributed to its low duty cycle (<1%).…”
Section: Discussionmentioning
confidence: 93%
“…Perhaps surprisingly, the correlation between the CRAFTI data and the EHS cross sections is somewhat better (as measured via R 2 , Table 2) than the correlation observed for any of the IMS data sets [4][5][6], despite the fact that the computed cross sections were designed to reproduce IMS results. The same is true when the various experimental measurements are correlated with either the projection approximation or trajectory method calculations (data not shown), so this is not an artifact due to using the EHS method.…”
Section: Correlation Of Experimental Cross Sections With Cross Sectiomentioning
confidence: 86%
“…Cross sections for 20 singly protonated amino acid ions, measured using CRAFTI at a kinetic energy of 1.9 keV in the laboratory reference frame, are listed in Table 1, along with values computed from previously reported [4][5][6] reduced mobilities, values measured using TWIMS [7], and values from MOBCAL exact hard sphere scattering (EHS) calculations performed as described above (the MOBCAL projection approximation and trajectory methods give results quite similar to those of the EHS calculations, but we focus on EHS values because the CRAFTI experiments are conducted at energies where the hard sphere potential is probably the best description of the interaction between the neutral collision gas and the ion). The values from references [4][5][6] were calculated from the reduced ion mobilities reported therein using Equation 1 [23,24].…”
Section: Collision Cross Sections Of Protonated Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations